Tax Disputes - The Role of Technology and Controversy Expertise - Dyck, Daniel; Lorenz, Johannes; Sureth-Sloane, Caren

Tax Compliance Management Systems in German Tax Audits - An Analysis of Practical Experiences - Schulz, Kim Alina; Sureth-Sloane, Caren
Recent regulatory changes and the adoption of the ‘DAC 7’ EU Directive have significantly increased the importance of Tax compliance management systems (Tax CMS) in German tax audits. Our interview-based study, which draws on the insights of experts from various sectors, including industry and commerce on the one hand side and tax advisors on the other hand side, reveals nuanced perspectives on the impact of Tax CMS on tax audits. Our results reveal that the number of Tax CMS in German firms has increased in recent years and that, in particular, the majority of large firms have implemented these control systems. From a firm’s perspective, there has been no discernible impact on the duration, scope, or focus of tax audits, nor the frequency of tax disputes or the number and size of tax refunds. However, tax practitioners in advisory firms report a slight positive change in the audit environment, with fewer tax disputes, and a more efficiency-driven approach to audit procedures, with an increase in process-oriented audits. These findings represent preliminary observations on the use and effectiveness of Tax CMS in tax audits. They provide early insights into the advantages and disadvantages of these systems. These findings are particularly relevant given the expected increasing role of Tax CMS in German tax audits, driven by ongoing regulatory developments.

Auferstehung. Zum 150. Geburtstag von Walter Courvoisier (1875-1931) - Schroeter-Wittke, Harald (Praktische Theologie)

Tanken. Zum 100. Todestag von Hjalmar Borgström (1864-1925) - Schroeter-Wittke, Harald (Praktische Theologie)

Chromophore Induced Effects in Iron(III) Complexes - Schmitz, Lennart; Argüello Cordero, Miguel A.; Al-Marri, Mohammed J.; Schoch, Roland; Egold, Hans; Neuba, Adam; Steube, Jakob; Bracht, Bastian Johannes; Bokareva, Olga S.; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
In the search for noble metal free photocatalytic systems, iron is the dream candidate. To increase excited state lifetimes of iron complexes, the multichromophoric approach is promising, combining organic chromophores with photoactive iron complexes, potentially enabling a reservoir effect. We present a series of chromophore-functionalized complexes based on the parental FeIII complex [Fe(ImP)2][PF6] (HImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)). The four organic chromophores benzene, naphthalene, anthracene, and pyrene are attached to the ImP-ligand in para-position to the coordination site to systematically investigate the influence of the steric demand and electronic properties of the chromophore on charge transfer lifetimes as well as photodynamics. A thorough ground state characterization was conducted in addition to investigations of the excited state dynamics by transient absorption spectroscopy and streak camera emission measurements. The conclusions drawn are supported by extensive DFT calculations. The emission coefficients could be significantly improved by the addition of chromophores. After excitation of the complexes with larger chromophores, coplanarization of the backbone and complex motif occurs to stabilize the formal charge. This results in population of a superligand state that exhibits a much faster radiationless relaxation to the ground state compared to the parent complex, hindering a reservoir effect.
Keywords: Photo

Low Temperature Emissive Cyclometalated Cobalt(III) Complexes - Krishna, Athul; Fritsch, Lorena; Steube, Jakob; Argüello Cordero, Miguel A.; Schoch, Roland; Neuba, Adam; Lochbrunner, Stefan; Bauer, Matthias (Inorganic Chemistry)
A series of CoIII complexes [Co(RImP)2][PF6], with HMeImP = 1,1′-(1,3-phenylene)bis(3-methyl-1-imidazole-2-ylidene)) and R = Me, Et, iPr, nBu, is presented in this work. The influence of the strong donor ligand on the ground and excited-state photophysical properties was investigated in the context of different alkyl substituents at the imidazole nitrogen. X-ray diffraction revealed no significant alterations of the structures and all differences in the series emerge from the electronic structures. These were probed via cyclic voltammetry and UV–vis spectroscopy, detailing the influence of the different alkyl substituents on the ground-state properties. All complexes are emissive at 77 K from a 3MC state, which exhibits lifetimes in the range of 1–5 ns at room temperature, depending on the alkyl substituent. Therefore, it is clearly shown that even small differences in the electronic structure have a large impact on the details of the excited state landscape. The observed behavior was rationalized by a detailed DFT analysis, which shows that the minimum-energy crossing point to the ground-state is located only slightly above the MC energy: Consequently, nonradiative decay to the ground state at room temperature is enabled, while at 77 K this path is prohibited, leading to low-temperature 3MC emission.
Keywords: Photo

On "Super Likes" and Algorithmic (In)Visibilities: Frictions Between Social and Economic Logics in the Context of Social Media Platforms - Schulz, Christian (Digital Culture & Society)

Contrastive Verbal Guidance: A Beneficial Context for Attention To Events and Their Memory? - Singh, Amit; Rohlfing, Katharina J. (Cognitive Science)
Research suggests that presenting an action via multimodal stimulation (verbal and visual) enhances its perception. To highlight this, in most studies, assertive instructions are generally presented before the occurrence of the visual subevent(s). However, verbal instructions need not always be assertive; they can also include negation to contrast the present event with a prior one, thereby facilitating processing—a phenomenon known as contextual facilitation. In our study, we investigated whether using negation to guide an action sequence facilitates action perception, particularly when two consecutive subactions contrast with each other. Stimuli from previous studies on action demonstration were used to create (non)contrastive actions, that is, a ball following noncontrastive and identical (Over–Over or Under–Under) versus contrastive and opposite paths (Over–Under or Under–Over) before terminating at a goal location. In Experiment 1, either an assertive or a negative instruction was provided as verbal guidance before onset of each path. Analyzing data from 35 participants, we found that, whereas assertive instructions facilitate overall action recall, negating the later path for contrastive actions is equally facilitative. Given that action goal is the most salient aspect in event memory due to goal-path bias in attention, a second experiment was conducted to test the effect of multimodal synchrony on goal attention and action memory. Experiment 2 revealed that when instructions overlap with actions, they become more tailored—assertive instructions effectively guide noncontrastive actions, while assertive–negative instruction particularly guides contrastive actions. Both studies suggest that increased attention to the goal leads to coarser perception of midevents, with action-instruction synchrony modulating goal bias in real-time event apprehension to serve distinct purposes for action conceptualization. Whereas presenting instructions before subactions attenuates goal attention, overlapping instructions increase goal attention and reveal the selective roles of assertive and negative instructions in guiding contrastive and noncontrastive actions.

Nachträgliche Gegenwart. Zur Rezeption Paul Celans in Frédéric Brenners "ZERHEILT" - Spener, Anna Maria (Celan-Perspektiven 2023: Transformationen Celans in der Kunst der Gegenwart)

The Intrapreneur Identity Illusion: Unraveling the Identity Work of Intrapreneurs in Internal Corporate Venturing - Starmann, Frederic-Alexander; Tomin, Slawa; Hubner-Benz, Sylvia; Kabst, Rüdiger (Journal of Product Innovation Management)
ABSTRACT Intrapreneurs—employees participating in internal corporate venturing (ICV) programs—are vital in nurturing entrepreneurship within organizations. While existing literature has extensively studied ICV at the organizational level, research on individual‐level processes remains limited, particularly regarding intrapreneurs' identity‐related conflicts over time. However, to design programs and interventions that unlock employees' creative potential and promote innovation, it is crucial to understand these individual dynamics. We conducted an 18‐month longitudinal study of 21 intrapreneurs within an ICV program, developing a process model and theory of intrapreneurs' identity work. We find that aspiring intrapreneurs construct an “idealized entrepreneur identity” that fundamentally conflicts with their employee identity. To maintain a coherent sense of self, they either safeguard their emerging entrepreneur identity by denying corporate dependence and eventually opposing the organization or they realign with their employee role, forsaking their intrapreneurial aspirations. These findings challenge the implicit assumption of a distinct intrapreneur identity, demonstrating how and why intrapreneurs struggle to construct a coherent and positively valued identity as intrapreneurs. We term this phenomenon the intrapreneur identity illusion and highlight its detrimental effects for both individuals and organizations. Our research contributes to understanding the individual‐level foundations of corporate entrepreneurship and offers broader implications for innovation management.

Unveiling the Impact of Cultural Value Orientations on Ideation Outcomes: Evidence From the International #EUvsVirus Hackathon - Krebs, Benjamin P.; Funck, Marieke; Tomin, Slawa; Wach, Bernhard; Kabst, Rüdiger (R&D Management)
ABSTRACT This study addresses the role of national culture in shaping hackathon teams' ideation outcomes. Drawing on the innovation and creativity literature and Schwartz’ theory of cultural value orientations, we propose that hierarchical values decrease the quality of ideas that teams develop over the course of a hackathon and that intellectual autonomy and mastery improve it. Using archival data, including pitch presentations from an international hackathon and data on cultural value orientations, we compiled a sample of 308 teams to investigate the influence of cultural value orientations and employed linear mixed‐effects regression analysis to test our hypotheses. We found that hierarchical cultural values are negatively associated with the quality of ideas, which suggests that hackathon teams that operate in such cultures suffer from a “liability of hierarchy.” We also found that teams from societies that emphasize mastery of the natural and social environment are more likely than other teams are to develop high‐quality ideas to tackle the (grand) challenges that hackathons address. We found no relationship between intellectual autonomy and idea quality. The study findings support the notion that culture manifests in hackathon teams' behavior and so shapes the quality of ideas they develop, thus laying the foundation for success or failure.

The Intrapreneur Identity Illusion: Unraveling the Identity Work of Intrapreneurs in Internal Corporate Venturing - Starmann, Frederic‐Alexander; Tomin, Slawa; Hubner‐Benz, Sylvia; Kabst, Rüdiger (Journal of Product Innovation Management)
ABSTRACT Intrapreneurs—employees participating in internal corporate venturing (ICV) programs—are vital in nurturing entrepreneurship within organizations. While existing literature has extensively studied ICV at the organizational level, research on individual‐level processes remains limited, particularly regarding intrapreneurs' identity‐related conflicts over time. However, to design programs and interventions that unlock employees' creative potential and promote innovation, it is crucial to understand these individual dynamics. We conducted an 18‐month longitudinal study of 21 intrapreneurs within an ICV program, developing a process model and theory of intrapreneurs' identity work. We find that aspiring intrapreneurs construct an “idealized entrepreneur identity” that fundamentally conflicts with their employee identity. To maintain a coherent sense of self, they either safeguard their emerging entrepreneur identity by denying corporate dependence and eventually opposing the organization or they realign with their employee role, forsaking their intrapreneurial aspirations. These findings challenge the implicit assumption of a distinct intrapreneur identity, demonstrating how and why intrapreneurs struggle to construct a coherent and positively valued identity as intrapreneurs. We term this phenomenon the intrapreneur identity illusion and highlight its detrimental effects for both individuals and organizations. Our research contributes to understanding the individual‐level foundations of corporate entrepreneurship and offers broader implications for innovation management.

Unveiling the Impact of Cultural Value Orientations on Ideation Outcomes: Evidence From the International #EUvsVirus Hackathon - Krebs, Benjamin P.; Funck, Marieke; Tomin, Slawa; Wach, Bernhard; Kabst, Rüdiger (R&D Management)
ABSTRACT This study addresses the role of national culture in shaping hackathon teams' ideation outcomes. Drawing on the innovation and creativity literature and Schwartz’ theory of cultural value orientations, we propose that hierarchical values decrease the quality of ideas that teams develop over the course of a hackathon and that intellectual autonomy and mastery improve it. Using archival data, including pitch presentations from an international hackathon and data on cultural value orientations, we compiled a sample of 308 teams to investigate the influence of cultural value orientations and employed linear mixed‐effects regression analysis to test our hypotheses. We found that hierarchical cultural values are negatively associated with the quality of ideas, which suggests that hackathon teams that operate in such cultures suffer from a “liability of hierarchy.” We also found that teams from societies that emphasize mastery of the natural and social environment are more likely than other teams are to develop high‐quality ideas to tackle the (grand) challenges that hackathons address. We found no relationship between intellectual autonomy and idea quality. The study findings support the notion that culture manifests in hackathon teams' behavior and so shapes the quality of ideas they develop, thus laying the foundation for success or failure.

Quantitative and Qualitative Literature Review of Augmented Reality in Teaching - Alptekin, Mesut; Froese, Lennart; Temmen, Katrin (Recent Trends of AI Technologies and Virtual Reality: Proceedings of 8th International Conference on Artificial Intelligence and Virtual Reality (AIVR 2024))
At Paderborn University, an AR-based app is being developed to prepare electrical engineering students for laboratory work. This paper aims to review the development of AR since 2010, particularly in technical university laboratories, through a systematic literature review. The study investigates AR's relevance in university teaching and examines specific AR applications in laboratory settings. Using a mixed-method approach, the research first employs a web crawler to gather 27,249 articles from the Lens database, followed by a bibliometric analysis. Further, Google Scholar is used to find 374 articles related to AR in scientific and technical laboratories, with 51 significant ones evaluated for application areas, findings, and other criteria. The findings show that AR in education is a growing trend, with a significant increase in publications and citations in recent years. Most studies focus on marker-based mobile AR applications, assessing aspects like motivation and user experience through surveys and interviews. However, there's limited research on AR's learning effectiveness in laboratories, partly due to the scarcity of technical equipment. One study found no significant learning impact from AR.
Keywords: Augmented Reality; Mixed Reality; Literature Review; Bibliometric Analysis; Education \and Laboratories

Revealing the Unspoken: Using LLMs to Mobilize and Enrich Tacit Knowledge in Event Logs of Knowledge-Intensive Processes - Brennig, Katharina (AMCIS 2025 Proceedings. 11.)
Large Language Models (LLMs) excel in understanding, generating, and processing human language, with growing adoption in process mining. Process mining relies on event logs that capture explicit process knowledge; however, knowledge-intensive processes (KIPs) in domains such as healthcare and product development depend on tacit knowledge, which is often absent from event logs. To bridge this gap, this study proposes a LLM-based framework for mobilizing tacit process knowledge and enriching event logs. A proof-of-concept is demonstrated using a KIP-specific LLM-driven conversational agent built on GPT-4o. The results indicate that LLMs can capture tacit process knowledge through targeted queries and systematically integrate it into event logs. This study presents a novel approach combining LLMs, knowledge management, and process mining, advancing the understanding and management of KIPs by enhancing knowledge accessibility and documentation.
Keywords: Process Mining; Large Language Model; Knowledge Management; Knowledge-Intensive Process; Tacit Knowledge

Vancomycin‐Modified DNA Origami Nanostructures for Targeting Bacterial Pathogens - Coşkuner Leineweber, Özge; Pothineni, Bhanu K.; Schumann, Nils; Hofmann, Ulrike; Möser, Christin; Smith, David M.; Grundmeier, Guido; Zhang, Yixin; Keller, Adrian (Small Structures)
The specific binding of DNA origami nanostructures (DONs) to bacteria is an important prerequisite for their application in pathogen targeting and antimicrobial drug delivery. So far, targeting bacteria with DONs has been achieved exclusively via aptamers, which suffer from drawbacks such as sensitivity toward environmental conditions and reduced binding after immobilization or conjugation. Here, an alternative approach is presented based on the modification of DONs with the cell wall‐binding glycopeptide antibiotic vancomycin. Using strain‐promoted azide‐alkyne cycloaddition, azide‐modified vancomycin is conjugated to selected staple strands and subsequently incorporated into 2D DON triangles. The resulting constructs show specific binding to the Gram‐positive species Bacillus subtilis ( B. subtilis ) and Staphylococcus capitis ( S. capitis ), and remarkably, to Gram‐negative Escherichia coli ( E. coli ), but no antimicrobial activity at vancomycin concentrations up to at least 2.91 μM. For B. subtilis and E. coli , DONs with vancomycin modifications on both sides exhibit better binding than DONs modified on only one side. However, both variants bind equally well to S. capitis . These results demonstrate the great potential of small molecule drug compounds for the robust, broad‐spectrum targeting of bacteria with DONs. Targeting a ubiquitous cell wall component of most pathogenic bacteria, vancomycin‐modified DONs have many potential applications in the prevention and treatment of nosocomial infections.

Security Implications of Malicious G-Codes in 3D Printing - Rossel, Jost; Mladenov, Vladislav; Wördenweber, Nico; Somorovsky, Juraj (Proceedings of the 34th USENIX Security Symposium)
The rapid growth of 3D printing technology has transformed a wide range of industries, enabling the on-demand production of complex objects, from aerospace components to medical devices. However, this technology also introduces significant security challenges. Previous research highlighted the security implications of G-Codes—commands used to control the printing process. These studies assumed powerful attackers and focused on manipulations of the printed models, leaving gaps in understanding the full attack potential. In this study, we systematically analyze security threats associated with 3D printing, focusing specifically on vulnerabilities caused by G-Code commands. We introduce attacks and attacker models that assume a less powerful adversary than traditionally considered, broadening the scope of potential security threats. Our findings show that even minimal access to the 3D printer can result in significant security breaches, such as unauthorized access to subsequent print jobs or persistent misconfiguration of the printer. We identify 278 potentially malicious G-Codes across the attack categories Information Disclosure, Denial of Service, and Model Manipulation. Our evaluation demonstrates the applicability of these attacks across various 3D printers and their firmware. Our findings underscore the need for a better standardization process of G-Codes and corresponding security best practices.

Improving wearable-based seizure prediction by feature fusion using an explainable growing network - Hasija, Tanuj; Kuschel, Maurice; Jackson, Michele; Dailey, Stephanie; Menne, Henric; Reinsberger, Claus; Vieluf, Solveig; Loddenkemper, Tobias (Artificial Intelligence in Medicine)

Centrifugal Differential Mobility Analysis—Validation and First Two-Dimensional Measurements - Rüther, Torben Norbert; Gröne, Sebastian; Dechert, Christopher; Schmid, Hans-Joachim (Powders)
To obtain a more comprehensive understanding of the specific properties of complex-shaped technical aerosols—such as partially sintered aggregates formed in combustion processes or structured particles resulting from complex synthesis processes—it is essential to measure more than a single equivalent size. This study examines a novel method for determining a two-dimensional distribution of two distinct particle properties within the size range from 50nm to 1000nm: the Centrifugal Differential Mobility Analyzer (CDMA). The CDMA enables the simultaneous measurement of both mobility and Stokes equivalent diameters, providing a detailed two-dimensional particle property distribution. This, in turn, allows for the extraction of shape-related information, which is essential for characterizing particles in terms of their chemical composition, reactivity, and other physicochemical properties. This paper presents a detailed evaluation of a first CDMA prototype. First, CFD simulations of the flow field within the classifier are presented in order to assess and understand non-idealities arising from the exact geometry. Subsequently, the transfer function is evaluated by particle trajectory calculations based on the simulated flow field. It can be demonstrated that the simulated transfer functions agree quite well with transfer functions derived from streamlines of an ideal flow field, indicating that the non-idealities in the classifying region are almost negligible in their effect on the classification result. An experimental determination of the transfer function shows additional effects not covered by the previous simulations, like broadening by diffusion and losses due to diffusion and precipitation within the in- and outlet of the classifier. Finally, the determined transfer functions are used to determine the full two-dimensional distribution with regard to the mobility and Stokes equivalent diameter of real aerosols, like spherical particles and aggregates at different sintering stages, respectively.
Keywords: centrifugal differential mobility analysis; 2D-measurement; particle characterization; moving reference frame CFD-simulation; transfer function

The Centrifugal Differential Mobility Analyser – concept and initial validation of a new device for measuring 2D property distributions - Rüther, Torben N.; Rasche, David B.; Schmid, Hans-Joachim (Aerosol Research)
Abstract. Usually for the characterization of nanoparticles, an equivalent property is measured, e.g. the mobility-equivalent diameter. In the case of non-spherical, complex-shaped nanoparticles, one equivalent particle size is not sufficient for a complete characterization. Most of the methods utilized to gain deeper insight into the morphology of nanoparticles are very time-consuming and costly or have bad statistics (such as tandem setups or TEM (transmission electron microscopy)/SEM (scanning electron microscopy) images). To overcome these disadvantages, a prototype of a new compact device, the Centrifugal Differential Mobility Analyser (CDMA), was built, which can measure the full 2D distribution of mobility-equivalent and Stokes equivalent diameters by classification in a cylinder gap through electrical and centrifugal forces. An evaluation method to determine the transfer probabilities is developed and used in this work to compare the measurement results with the theory for the pure rotational behaviour (like the Aerodynamic Aerosol Classifier) and the pure electrical behaviour (like the Dynamic Mobility Analyser). In addition, the ideal 2D transfer function was derived using a particle trajectory approach. This 2D transfer function is a prerequisite for obtaining the full 2D particle size distribution from measurements by inversion.